Influence of Audit Tenure, Profitability, Solvency, and Company Size on Audit Delay in the Indonesian Stock Exchange Period 2020-2022 - Hansela, Yolanda; Sembiring, Novelina; Saragi, Sandi Kamelia; Putri, Arie Pratania; Ovam, Debbi Chyntia (Lembaga Riset Ilmiah, 2023)
Company mining is a company That does activity exploration source Power natural for obtaining profit. Study This aims To analyze the Influence of Auditing Tenure, Profitability, Solvency, And Size Company To Auditing Delay On Company Mining Registered in Exchange Effect Indonesia (IDX) Period 2020-2022. In the study This use technique of purposive sampling For obtain as many as 51 companies mining listed on the Stock Exchange Effect Indonesia (IDX) 2020-2022 period. In testing the hypothesis of the study, obtained results in a way partial and simultaneous. Results obtained in a way Partial to study Which has done variable Auditing Tenure And Solvency influential significant to Auditing Delay. The temporary second variable other that Profitability and Company Size has no effect significant to Audit Delay in Registered Mining Companies in Bursa Effect Indonesia (IDX) Period 2020-2022